(3QSGdI aj Gdabgs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3eHGOdI eGd HeGd hCeG GdCNjQ adG ETcGd aj chfg eLGRG ef SGHbg ef HGH EWdGb GSe GdSHH Ydi GdeSHH Ke dG jNai eG aj JYQja GdeUHGM ef GdeSGeMIs
(3BNQgG (B:s
(3BNQgG(B: (3hGdGSJTcGd aj GdKGfj Ch GdaJhi HUMJg ef LgI Cf GdNUhUjI EfeG gj HWjH GdfaS aj ZjQ eMdg Hd eYdhe (B... (3adGHO ef JhLjg aJhi GdbhGYOs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis